Paleomagnetism of the Late Proterozoic sills in the Tsezotene Formation, Mackenzie Mountains, Northwest Territories, Canada - Park, J. K. (Canadian Journal of Earth Sciences, 1981)
A paleomagnetic study was conducted on a regionally extensive diabase sill intruding the upper part of the Helikian (?) Tsezotene Formation located in the Mackenzie Mountains Supergroup of northwestern Canada. Twelve sites, one from a lower sill at one locality, were sampled over a distance of about 200 km. Two general magnetizations presumably carried by maghemite (A R : 38 specimens; 272°, 00°; pole 139°E, 01°N; K = 34, A 95 = 4°) and hematite (B: 18 specimens; 269°, −01°; pole 141°E, 01°S; K = 21, A 95 = 7°) were resolved by using a two-stage treatment method (alternating field treatment of 20–45 mT followed by thermal demagnetization to about 650 °C) in combination with vector subtraction and vector diagrams. B has normal (B N : 6 specimens) and reverse (B R : 17 specimens) components. Another magnetization (R M : 30 specimens; 086°, + 55°; k = 3) carried by magnetite appears to be a resultant of normal and reverse components, though it may include a secondary Cretaceous component. It is likely that the maghemite and hematite are deuteric alteration products of the magnetite and that they retain the primary direction probably residing in the unresolved magnetite components of R M .